Analisis Penetapan Harga Jual Berdasarkan Metode Cost Plus Pricing (Studi Kasus pada Rumah Makan Raja Muda Kabupaten Pangkajene dan Kepulauan) - Nabilah Nur Rizqikah; Abdul Rijal; Hariany Idris (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to analyze the determination of selling prices based on the cost plus pricing method at Raja Muda Restaurant, Pangkajene Regency and Islands. Each restaurant sets very different prices and the way they set those prices also varies. Cost plus pricing is one of the methods used to determine the selling price. The type of research used in this study is a type of qualitative research. The sample of this study is the expenditure record of the Raja Muda Restaurant in October 2023 in Pangkajene and Islands Regency. Data collection was carried out using documentation and interview techniques. Data analysis was carried out by descriptive analysis. The results of this study show that in determining the selling price according to the cost plus pricing method by adding the total cost and mark up by 30.11% and the calculation results are greater than the method applied by restaurant owners with a difference of Rp 253